1993
DOI: 10.2307/1940818
|View full text |Cite
|
Sign up to set email alerts
|

Suspended Clays Alter Trophic Interactions in the Plankton

Abstract: This paper explores how suspended clays alter the trophic interactions that govern composition and density of the zooplankton community in a small eutrophic North Carolina (USA) lake. Enclosures (12m 3 ) were used in a complete, triplicated, cross-classified design. The four treatments were; BASS (1 piscivorous fish/enclosure), BASS + CLAY, SUNFISH (16 planktivorous fish/enclosure), SUNFISH+ CLAY. The +CLAY treatments received 100 g·m-2 ·d-1 of montmorillonitic clay. It was anticipated that turbidity from clay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 37 publications
0
22
1
Order By: Relevance
“…Marinelarena & Giorgi (2001) observed rapid uptake of dissolved phosphorus regardless of differences in light, temperature, and periphyton community composition. Long-term exposure to clays with sorbed SRP affected algal growth and species composition (Cuker, 1993); however, rates of SRP uptake were unaffected. Similarly, we found no differences between periphyton SRP uptake in lotic systems containing suspended clay and those without.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marinelarena & Giorgi (2001) observed rapid uptake of dissolved phosphorus regardless of differences in light, temperature, and periphyton community composition. Long-term exposure to clays with sorbed SRP affected algal growth and species composition (Cuker, 1993); however, rates of SRP uptake were unaffected. Similarly, we found no differences between periphyton SRP uptake in lotic systems containing suspended clay and those without.…”
Section: Discussionmentioning
confidence: 99%
“…Runoff carrying eroded clays creates turbid conditions that reduce light intensities and smother benthic substrates in the aquatic habitat (Parkhill & Gulliver, 2002). These physical changes subsequently affect nutrient-biota processes, at least in part through lowered photosynthetic potential but also through diverse sorption-desorption reactions (Cuker, 1993;Lind, 2003). Major changes in the structure and function of stream benthic and periphytic communities can occur in response to increased inputs of clays and fine sediments (Graham, 1990;Horner et al, 1990;Power & Stewart, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Higher nutrient concentrations might be linked to higher concentrations of suspended particles. Many studies demonstrated interactions between particulate matter and ions or nutrients (e.g., Cuker et al 1990;Fukushima et al 1991;Cuker 1993;Mez et al 1998) and concluded that particulates can have strong effects on the nutrient situation in the lake and the phytoplankton community. Suspended particular matter entail also a different underwater light quality.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, turbidity has been viewed as one of the most important regulators of species interactions, and in turn community structure, in aquatic ecosystems (Cuker 1993, Aksnes et al 2004, Horppila and Liljendahl-Nurminen 2005. Further, owing to continued watershed development, which has increased the delivery of sediments and productivity-limiting nutrients to rivers and downstream (recipient) ecosystems, the importance of turbidity as a community structuring mechanism has increased and likely will continue to do so with sustained climate-driven increases precipitation and runoff (Nelson et al 2009, Rabalais et al 2009).…”
Section: Introductionmentioning
confidence: 99%